THE INFLUENCE OF FINANCIAL TECHNOLOGY, FINANCIAL LITERACY, SELF-CONTROL, LIFESTYLE ON THE FINANCIAL MANAGEMENT BEHAVIOR OF GENERATION Z IN SURABAYA CITY - Ramadhani, Dela Sifa; Pramudianti, Mira (Journal of Industrial Engineering & Management Research, 2026)
This study aims to analyze the influence of financial technology, financial literacy, self-control, and lifestyle on the financial management behavior of Generation Z in Surabaya. This study used a quantitative approach with a survey method. The sampling technique used was purposive sampling with certain criteria, resulting in 105 respondents. Data collection was carried out through the distribution of questionnaires using Google Forms. The data analysis technique used in this study was multiple linear regression analysis. The results showed that financial technology, financial literacy, self-control, and lifestyle jointly influence financial management behavior, while financial technology and lifestyle partially do not influence financial management behavior.